STUDI KASUS: DIABETES MELITUS DISERTAI KOMPLIKASI CONGESTIVE HEART FAILURE (CHF) - Supatmi, Supatmi; Novita Kumalasari, Dian; Wulandari, Anisa (Yayasan Healing and Healthcare Education, 2023)
The International Diabetes Federation (IDF) estimates that at least 463 million people aged 20-79 years in the world have diabetes in 2019, or the equivalent of a prevalence rate of 9.3% of the total population at the same age. Indonesia is ranked 7th among 10 countries with the highest number of DM sufferers, which is 10.7 million.The method used is descriptive method using case studies. The study was conducted in the Abimanyu Room, Panembahan Senopati Regional General Hospital using 1 participant with a Medical Diagnosis of Diabetes Mellitus accompanied by complications of Congestive Heart Failure (CHF) and with the main Nursing Diagnosis of Ineffective Breathing Pattern. After continuous nursing care for three days with good cooperation between the nurse and the patient and the patient's family, as well as with other health teams, it can be concluded that from the results of the study, there were seven nursing diagnoses that appeared in the patient, Mr. M. There are four problems in theory and cases. Two problems exist in theory but not in Mr. M. Three problems do not exist in theory but arise in the case of Mr. M. planning is made and determined according to the nursing problems that arise. The implementation of nursing care in collaboration with other health teams and the patient's family, with the evaluation results of the seven problems, three problems were resolved and four problems were partially resolved. Cconclusions from the nursing care that has been carried out on Mr. M with Diabetes Mellitus accompanied by complications of Congestive Heart Failure (CHF) was found seven nursing problems, out of seven nursing diagnoses three diagnoses were resolved, namely acute pain, sleep pattern disturbance, risk of infection. and there were four partially resolved diagnoses, namely ineffective breathing patterns, decreased cardiac output, unstable blood glucose levels, activity intolerance.